Differing Pattern of Ambulatory Blood Pressure in Very Elderly Men Expresses Dynamics in Atherosclerotic Load in the Senescence - Arkadiusz Siennicki-Lantz; Sölve Elmståhl (International Journal of Hypertension)
To assess an impact of vascular risk factors on ambulatory blood pressure measurement (ABPM) in the elderly, we followed up a population-based cohort of men from 68 until 82 years, when 104 survivors underwent ABPM. Results. At age 68, hypertension and high clinic blood pressure (CBP) did not predict ABPM level. Smoking and low ankle-brachial index (ABI) predicted higher ABPM variability and pulse pressure (PP), but not absolute ABPM values. At age 82, hypertension, high or increasing CBP, strongly positively correlated with all variables of ABPM. Carotid stenosis, low or declining ABI during followup, correlated with higher nocturnal ABPM and PP. Concluding. Hypertension and vascular risk factors in a cohort of 68-year-old men do not result in higher ABPM at age 82, possibly due to inflection point in their pressure development. Higher ABPM reflects instead an increasing CBP and aggravating atherosclerosis during the preceding decade in that part of the cohort with previously favorable risk factor status.